The complete mitochondrial genome of Schisandra sphenanthera (Schisandraceae) - Xianxian Yu; Yanlei Feng; Wei Zhai; Min Chen; Guoxi Wu (Mitochondrial DNA. Part B. Resources, 2018)
Schisandra sphenanthera (Austrobaileyales) is a famous traditional Chinese medicine being long-history used, is also one of early-diverging angiosperms and important links to uncover the early evolution of angiosperms. Here the complete mitochondrial genome of S. sphenanthera was obtained for the first time. It is 1,106,521 bp in length with 46.4% GC content. It contains 58 genes, including 41 protein coding genes, three ribosomal RNA genes and 14 transfer RNA genes. Phylogenetic analysis indicated that S. sphenanthera was placed in the basal angiosperm just after Amborella and Nuphar. The mitogenome of S. sphenanthera would provide a reliable genetic and evolutionary resource.